Hot and Cold Smells: Odor-Temperature Associations across Cultures - Wnuk, Ewelina; de Valk, Josje M.; Huisman, John L. A.; Majid, Asifa (Frontiers in Psychology, 2017)
It is often assumed odors are associated with hot and cold temperature, since odor processing may trigger thermal sensations, such as coolness in the case of mint. It is unknown, however, whether people make consistent temperature associations for a variety of everyday odors, and, if so, what determines them. Previous work investigating the bases of cross-modal associations suggests a number of possibilities, including universal forces (e.g., perception), as well as culture-specific forces (e.g., language and cultural beliefs). In this study, we examined odor-temperature associations in three cultures—Maniq (N=11), Thai (N=24), and Dutch (N=24)—who differ with respect to their cultural preoccupation with odors, their odor lexicons, and their beliefs about the relationship of odors (and odor objects) to temperature. Participants matched 15 odors to temperature by touching cups filled with hot or cold water, and described the odors in their native language. The results showed no consistent associations among the Maniq, and only a handful of consistent associations between odor and temperature among the Thai and Dutch. The consistent associations differed across the two groups, arguing against their universality. Further analysis revealed cross-modal associations could not be explained by language, but could be the result of cultural beliefs.